Evaluating the Benefits of Using Mobile Application (diarrhea management step by step) in the Management of Diarrhea by Community Pharmacists - Mikhael, Ehab Mudher; Fadya Yaqoob Al-Hamadani; Ali Mohammed Hadi (Iraqi Journal of Pharmaceutical Sciences, 2023)
Diarrhea is one of the most commonly encountered minor ailments in the community pharmacies. It is associated with significant morbidity and mortality. However, the majority of pharmacists in Iraq did not manage diarrheal cases in a proper way. Therefore, the current study aimed to evaluate the benefit of a new mobile application (diarrhea management step by step) to improve the pharmacist’s role in the management of diarrhea. The study was conducted from 21th September to 21th October 2021 using a pre-post design via a simulated patient (SP) technique. A validated diarrhea scenario was presented to each pharmacist by the SP twice, once before and the other after giving the mobile application to the pharmacist. Furthermore, pharmacists were asked to rate the application in regard to its ease of use, reducing the time needed for management of diarrhea cases, reducing diagnostic errors, reducing medication errors, and applicability in daily clinical practice. The study sample involved 50 community pharmacists. However, only 47 completed the study. After using the application, all questions necessary to assess diarrhea were significantly improved. Moreover, the average number of questions asked to the SP was significantly increased. On the other hand, providing the SP with an appropriate non-pharmacological and pharmacological treatment was also significantly improved. Additionally, counseling the SP with the necessary information about dispensed medication was improved; however, significant improvement was detected only in regard to information about the drug dose and dosing frequency. Most participated pharmacists strongly agreed with the application ease of use, its ability to reduce diagnosis and medication errors, and its applicability for use in daily clinical practice. In conclusion the tested application is an effective method to improve the pharmacist’s role in the assessment and management of diarrhea.